Temporal changes in wood density of Norway spruce in southern Finland : evidence from National Forest Inventory data - Mäkinen, Harri; Nöjd, Pekka; Räty, Minna; Heräjärvi, Henrik (Springer Nature, 2026)
The annual volume increment in Finland has doubled over the past 100 years, primarily due to more efficient stand management practices. However, few studies have examined how wood density, an important parameter of wood quality, responds to changes in forest management and site conditions on a large scale. We compared the wood density of Norway spruce (Picea abies (L.) Karst.) in current stands to that 20 years earlier in southern Finland. Our analyses are based on extensive, statistically representative Finnish National Forest Inventory (NFI) data. Wood density profiles were measured from pith to bark on NFI cores sampled in 1999 and from 2018 to 2020. The results illustrated that young trees have grown 2–3 times faster in recent decades than in the past. This increased growth rate has not led to a noteworthy decrease in average wood density over time. However, at the level of individual trees, wood density around the pith decreased as the radial increment rate increased. Therefore, increasing the radial growth of young trees has negative consequences for wood density. An additional millimetre in the width of the innermost annual rings caused a 10–40 kg/m3 decrease in density, with the change being greater the narrower the rings were. The difference between naturally regenerated and planted trees was not statistically significant; however wood density was lower in relatively fertile sites compared to medium-fertile sites. Our results suggest that, on a large scale, the more recently applied forest management methods have not decreased the average wood density compared to older methods. However, the radial increment of juvenile trees is faster, which results in a reduction of their wood density.
Keywords: forest management; radial increment; wood properties